Pregnancy loss and risk of ischaemic stroke and myocardial infarction. (7th April 2016) - Maino, Alberto; Siegerink, Bob; Algra, Ale; Martinelli, Ida; Peyvandi, Flora; Rosendaal, Frits R.
Abstract : We investigated whether pregnancy loss increases the risk of arterial thrombosis in young women. Women (age 18–50 years) with ischaemic stroke (IS) or myocardial infarction (MI) and at least one pregnancy were compared for pregnancy loss in a control group. Odds ratios (OR) with 95% confidence intervals (CI), adjusted for matching variables, cardiovascular risk factors, cardiovascular family history and the presence of antiphospholipid antibodies, were calculated for the number of pregnancy losses as well as the type of unsuccessful pregnancy (early miscarriage, late miscarriage and stillbirth). 165 IS cases, 218 MI cases and 743 controls were included. Women with multiple (≥3) pregnancy loss had a doubled risk of arterial thrombosis (OR 2·37, 95%CI 0·99–5·70) compared with women without pregnancy loss, similarly to women who experienced stillbirth (OR 1·68, 95%CI 0·79–3·55). Both relative risks were higher for IS (OR 3·51, 95%CI 1·08–11·35 and 2·06, 95%CI 0·81–5·23, respectively) than for MI (OR 2·04, 95%CI 0·71–5·86 and 1·04, 95%CI 0·39–2·79). Adjustment for antiphospholipid antibodies did not affect the estimates. Multiple pregnancy loss and stillbirth increases the risk of IS and, to a lesser extent, of MI, even when other cardiovascular risk factors and antiphospholipid antibodies are accounted for.